2020
DOI: 10.1111/jse.12597
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and biogeography ofDiapensia(Diapensiaceae) based on chloroplast genome data

Abstract: Diapensia L. is the second largest genus of Diapensiaceae. The taxonomic treatment within Diapensia and relationships within Diapensiaceae have been disputed. Chloroplast genome sequence data have proved to be useful for plant phylogenetic analyses and species delimitation. In this study, we de novo sequenced and assembled 22 chloroplast genomes of 15 species of Diapensiaceae, including all recognized species of Diapensia with multiple samples. A super‐matrix containing a total of 107 genes and 18 taxa was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Similar to Higashi et al (2015), we found that Schizocodon and Shortia are both monophyletic. The general topology we recovered on the basis of combined nuclear and plastid data set agrees with plastome‐based inferences for the family (Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Similar to Higashi et al (2015), we found that Schizocodon and Shortia are both monophyletic. The general topology we recovered on the basis of combined nuclear and plastid data set agrees with plastome‐based inferences for the family (Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…The chloroplast genome is usually maternally inherited in most angiosperms and consists of two copies of inverted repeat (IR) regions divided by one small single‐copy region (SSC) and one large single copy region (LSC) (Bendich, 2004). With advancements in second generation sequencing technology, chloroplast genomes have been frequently used to address phylogenetic relationships among closely related species (Ma et al, 2020; Mu et al, 2020; Ye et al, 2020). The chloroplast genome contains sequence variation that can offer sufficient phylogenetic information to resolve closely related species, including species that have experienced complex evolution histories.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies enable simultaneous study of morphologically distinguishing characteristics for resolved clades in the phylogeny (Willis et al, 2017). All three studies (Hu et al, 2020;Su et al, 2020;Ye et al, 2020) clarified previous taxonomic debates in these taxa and enabled the authors to propose revised taxonomic treatments based on a large amount of molecular phylogenetic data. Furthermore, the phylogeny of Magnolia, in particular, provides a comprehensive framework that may prove useful in breeding programs in this horticulturally important genus.…”
Section: Editorialmentioning
confidence: 94%